The fate of the Kazakh aul in poetry at the beginning of the 20th century (based on Yessengali Raushanov’s poetry) - Aimukhambet Ж.Ә. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2024)
It is obvious that due to the Soviet policy, the Kazakh people were faced with a great disaster, the consequences of which continued for a century. At the beginning of the XX century, the aggressive policy of the Soviet government began to arrest educated and progressive people of the Kazakh nation, raising false accusations with false slander that they were “enemies of the people”, and terrorized the Kazakh steppe, leaving an indelible mark on the minds of people. Such a tragic period in the history of the country became a constant motif of many literary works. There are novels, stories, poems and dramatic works written on this subject. Among these works we can note the poetry of the Kazakh classical poet Essengali Raushanov. The article focuses on the poet’s works and analyzes the description of the fate of the Kazakh auls (village) at the beginning of the XX century in the cycle of poems “Kazakh Aul” and the poem “Aspanga koshyp ketken el” (Country that has moved into the sky). By analyzing these works, the questions about how the fate of the Kazakh country was reflected in this tragic period in the poet’s poetry, and how the poet expressed the sadness and grief of the country were answered. The plight of the Kazakh auls plundered by both the White and Red Armies has been considered in a combination of historical and artistic realities. The methods of comparison, induction and deduction have been used to study the topic. According to the requirements of the study, conclusions have been formulated and drawn.